Analysis of Goods Distribution in Increasing Sales Volume at CV Perindo in Gunungsitoli City - Gulo, Ardiven; Gea, Jeliswan Berkat Iman Jaya; Zebua, Serniati; Mendrofa, Martha Surya Dinata (ProBisnis : Jurnal Manajemen, 2025)
This study analyzes the role of goods distribution in increasing sales volume at CV. Perindo, located in Gunungsitoli City. The research focuses on identifying the distribution system applied by the company, the challenges faced in the process, and the solutions adopted to overcome these obstacles. Using a qualitative approach, data were collected through interviews, observations, and documentation involving stakeholders directly engaged in the distribution process. The findings reveal that CV. Perindo employs both direct and intermediary distribution channels, supported by a structured delivery schedule and a defined distribution coverage area. These mechanisms have proven effective in expanding market reach and boosting sales volume, especially in strategic regions. Nevertheless, the company still encounters barriers such as delayed delivery, transportation difficulties, and uneven product availability. To address these issues, CV. Perindo has taken corrective measures, including optimizing logistics management, expanding its delivery fleet, and conducting routine monitoring. The study concludes that a well-managed distribution system significantly contributes to sustaining and increasing sales volume, while also strengthening customer satisfaction and competitive advantage.